Common Fixed Point Results Using Generalized Altering Distances on Orbitally Complete Ordered Metric Spaces - Hemant Kumar Nashine; Zoran Kadelburg; Zorana Golubović (Journal of Applied Mathematics)
We prove the existence of common fixed points for three relatively asymptotically regular mappings defined on an orbitally complete ordered metric space using orbital continuity of one of the involved maps. We furnish a suitable example to demonstrate the validity of the hypotheses of our results.